Perceived self-efficacy and empowerment in patients at increased risk of sudden cardiac arrest - Davies, Brianna; Allan, Katherine S.; Carroll, Sandra L.; Gibbs, Karen; Roberts, Jason D.; MacIntyre, Ciorsti; Steinberg, Christian; Tadros, Rafik; Dorian, Paul; Healey, Jeff S.; Gardner, Martin; Laksman, Zachary W. M.; et al. (Frontiers in Cardiovascular Medicine, 2023)
Background: The role of multidisciplinary clinics for psychosocial care is increasingly recognized for those living with inherited cardiac conditions (ICC). In Canada, access to healthcare providers differ between clinics. Little is known about the relationship between access to speciality care and a patient’s ability to cope with, and manage their condition. Methods: We leveraged the Hearts in Rhythm Organization (HiRO) to conduct a cross-sectional, community based survey of individuals with ICC and their family members. We aimed to describe access to services, and explore the relationships between participants’ characteristics, cardiac history and self-reported health status and self-efficacy (GSE: General Self-Efficacy Scale) and empowerment (GCOS-24: Genetic Counseling Outcome Scale). Results: We collected 235 responses from Canadian participants in 10 provinces and territories. Overall, 63% of participants reported involvement of a genetic counsellor in their care. Access to genetic testing was associated with greater empowerment (mean GCOS-24: 121.14 (SD=20.53) vs. 105.68 (SD=21.69); p = 0.004). Uncertain genetic test results were associated with lower perceived self-efficacy (mean GSE: uncertain = 28.85 vs. positive = 33.16, negative = 34.13; p = 0.01). Low global mental health scores correlated with both lower perceived self-efficacy and empowerment scores, with only 11% of affected participants reporting involvement of psychology services in their care. Conclusion: Differences in resource accessibility, clinical history and self-reported health status impact the perceived self-efficacy and empowerment of patients with ICC. Future research evaluating interventions to improve patient outcomes is recommended.